General overview of the first 50 years of Economic Notes, 1972–2021. (1st February 2023) - Ferri, Giovanni
Abstract: We review the five different phases lived by Economic Notes during its first 50 years. First, its foundation and early phase—until 1983—received great support from Monte dei Paschi and also benefited from a windfall since Robert A. Mundell attracted to Siena an international network of top economists, policy makers and executives, facilitating high‐quality submissions to the Journal . When Mundell's meetings stopped (in 1978), Economic Notes had already secured a good reputation and had become a champion of a pluralist approach, accepting papers from different disciplines and views. In the second phase—from 1984 to the mid‐1990s—the Journal, led by a qualified Editorial Board lived continuity but also some new directions emerged. Economic Notes became better connected to the local Faculty of Economics. Also, the drive towards pluralism of the early years was refocused to safeguard access by different economic schools rather than different disciplines. In those years, Monte dei Paschi too transformed from a mostly regional bank into a national and international player, thus demanding less visibility support from the Journal . Those events blurred the initial mission and started distancing the Bank from the Journal . The third phase—from mid‐1990s to early 2000s—saw the maximum productivity and visibility of Economic Notes . Monte financed Conferences with great resonance also owing to an exceptional Advisory Board. In the fourth phase—from 2004, when the Conferences became rare, to 2012—the performance worsened. Communication between the Bank and the Journal grew more difficult, complicating any planning for the future. The fifth phase— from 2012 to 2019—aimed to relaunch the Journal without a significant support from the Bank, which had entered a period of difficulties of its own. The planned way out of this situation was to develop a series of Special Issues through dedicated Calls for Papers. As we show, that strategy delivered some results and, in effect, Economic Notes ' performance rebounded. Nevertheless, Monte was progressively disengaging from the Journal, which, eventually, was sold to Wiley, the publishing partner. The sixth and last phase of the Journal —from 2019 to 2021—under the new ownership by Wiley marked a gradual transformation. In the end, it seems that the publishing venture initiated in 1972 is still making progress and providing a pluralist forum for discussion. The journey of Economic Notes is still on!